Method for producing a halide solid-state electrolyte fiber membrane, fiber membrane and applications thereof
Patent Information
- Application Number
- CN202611478564.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-10-30
AI Technical Summary
目前卤化物固态电解质的主流制备方法为高能球磨法或固相合成法,通过上述方法制备的卤化物固态电解质均以颗粒状形式存在;在实际应用过程中,颗粒之间易形成天然间隙,难以构建连续的锂离子传输通道,导致离子传导效率大幅降低,无法充分发挥卤化物固态电解质的本征性能,严重制约了其在全固态锂离子电池中的产业化推广与应用
1、制备成本与周期降低:采用廉价原料,通过溶液前驱体法结合低温煅烧完成制备,相较传统高温固相法,大幅降低了合成温度、制备周期及整体使用成本;
Smart Images

Figure CN123018112A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of halide solid electrolyte fiber membrane technology, and more particularly to the preparation method of halide solid electrolyte fiber membrane, the fiber membrane and its application. Background Technology
[0002] Lithium-ion batteries, due to their superior characteristics of high energy density, long cycle life, and high operating voltage, have been widely used in consumer electronics and new energy fields. Their application scenarios have gradually expanded from portable electronic devices such as mobile phones, computers, and cameras to important areas such as emergency backup power, new energy vehicles, and large-scale energy storage. Traditional lithium-ion batteries generally use organic electrolytes as ion conduction media. Although these electrolytes have high ionic conductivity and charge / discharge efficiency, their inherent flammability and explosiveness pose serious safety hazards such as thermal runaway and short circuits during use, greatly limiting their large-scale application in high-power, large-capacity energy storage scenarios.
[0003] To address the safety concerns posed by organic electrolytes, replacing them with non-flammable solid electrolytes has become a core direction for the development of all-solid-state lithium-ion battery technology. Among these, halide solid electrolytes, as an emerging solid electrolyte system, possess high intrinsic ionic conductivity and excellent processing performance, meeting the practical application requirements of all-solid-state lithium-ion batteries and thus becoming a significant research hotspot in this field. Currently, the mainstream preparation methods for halide solid electrolytes are high-energy ball milling or solid-phase synthesis. Halide solid electrolytes prepared by these methods exist in particulate form. In practical applications, natural gaps easily form between particles, making it difficult to construct continuous lithium-ion transport channels. This leads to a significant reduction in ion conduction efficiency, failing to fully utilize the intrinsic performance of halide solid electrolytes and severely restricting their industrialization and application in all-solid-state lithium-ion batteries. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing halide solid electrolyte fiber membranes, the fiber membranes and their applications, and to solve the above-mentioned technical problems.
[0005] To achieve the above objectives, the present invention provides a method for preparing a halide solid electrolyte fiber membrane, comprising the following steps: S1. Preparation of halide solid electrolyte precursor solution: First, dissolve the polymer in a solvent to form a three-dimensional network molecular structure; then add the halide salt and stir to mix, so that the halide salt enters the gaps in the three-dimensional network molecular structure, is uniformly wrapped and dispersed by the polymer chain, and obtains a halide solid electrolyte precursor solution with uniform molecular-level dispersion. S2. Electrospinning: The halide solid electrolyte precursor solution is electrospinned to obtain a precursor fiber membrane. During electrospinning, a constant temperature hot field of 20℃-80℃ is applied in the spinning zone, while the temperature of the receiving device is controlled at 10℃-40℃. The fiber orientation is achieved by stretching the electrostatic field and pulling the receiving device to obtain the precursor fiber membrane. S3. Calcination: The obtained precursor fiber membrane is placed under a protective atmosphere and calcined to obtain a halide solid electrolyte nanofiber membrane.
[0006] Preferably, step S1 specifically includes the following steps: First, the polymer is dissolved in a solvent at a temperature of 0-100℃ and stirred continuously for 30-480 minutes. Then, the halide salt is added sequentially and stirring is continued for 20-480 minutes until all components in the system are mixed evenly to form a homogeneous precursor solution.
[0007] Preferably, the halide salt in step S1 includes a lithium source or sodium source and a metal source, and the molar ratio of the lithium source or sodium source, the metal source, the polymer and the solvent is 1~4∶4~1∶0.003-0.1∶1-300.
[0008] Preferably, the lithium source is at least one of lithium perchlorate, lithium carbonate, lithium acetate, and lithium chloride; The sodium source is at least one of sodium perchlorate, sodium carbonate, sodium acetate, and sodium chloride; The metal source is at least one of indium chloride, zirconium chloride, niobium chloride, ferric chloride, and lanthanum chloride; The polymer is at least one of polyvinyl butyral, polyvinyl acetate, polyvinylpyrrolidone, polyvinylidene fluoride, polyethylene oxide, and polyvinyl alcohol. The solvent is at least one of ethanol, acetonitrile, dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, tetrahydrofuran, and water.
[0009] Preferably, in step S2, the electrospinning process parameters are as follows: the relative humidity of the spinning environment is 5%-70%, the injection rate of the precursor solution is 0.1mL / h-10mL / h, the high voltage applied to the spinning field is 8kV-40kV, and the distance between the receiving device and the spinneret is 12cm-50cm.
[0010] Preferably, the receiving device is a metal roller, which achieves the directional alignment of precursor fibers by rotating.
[0011] Preferably, in step S3, the specific process of heating and calcining is as follows: the calcination temperature is gradually increased from room temperature to 100℃-600℃ at a heating rate of 0.1℃ / min-10℃ / min, and the temperature is held for 0-480min after reaching the highest calcination temperature.
[0012] The fiber membrane prepared by the method of preparing halide solid electrolyte fiber membrane is a halide solid electrolyte fiber membrane, and the average diameter of the fiber in the halide solid electrolyte fiber membrane is 50nm-800nm, the relative standard deviation of the fiber diameter is 1%-5%, and the grain size inside the fiber is 50nm-100nm. The ionic conductivity of halide solid electrolyte fiber membranes is >10. -3 S / cm.
[0013] Application of fiber membranes in solid-state batteries.
[0014] Therefore, the present invention, employing the above-mentioned method for preparing halide solid electrolyte fiber membranes, the fiber membranes, and their applications, has the following beneficial effects: 1. Reduced preparation cost and cycle: Using inexpensive raw materials, the preparation is completed through a solution precursor method combined with low-temperature calcination, which significantly reduces the synthesis temperature, preparation cycle and overall cost compared to the traditional high-temperature solid-state method. 2. Improved ion transport performance: The nanofiber structure provides a continuous channel for ion conduction, and the prepared fiber membrane has high ion conductivity, which solves the defect of discontinuous ion conduction between particles in traditional particulate halide solid electrolytes. 3. Excellent physical processing performance: The prepared halide solid electrolyte fiber membrane has good flexibility and moderate mechanical strength, good processability, and is suitable for the preparation and assembly requirements of solid lithium batteries. 4. Optimization of lithium battery interface and safety performance: The fiber membrane can achieve good interface performance with the electrode, while effectively suppressing the generation of lithium dendrites and foreign particles, greatly improving the safety of lithium-ion batteries. 5. Excellent electrochemical performance: The structure and composition design of the fiber membrane give it high stability, enabling it to achieve good electrochemical performance when applied to lithium batteries; 6. Wide range of applications: The prepared solid electrolyte nanofiber films have broad application prospects in the fields of all-solid-state lithium batteries and flexible lithium batteries, and the process is compatible with lithium and sodium source systems, which can be extended to prepare sodium-based halide solid electrolyte fiber films.
[0015] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0016] Figure 1 This is a flowchart illustrating the preparation method of the halide solid electrolyte fiber membrane according to the present invention. Figure 2The images shown are SEM images of the fiber membranes prepared in Example 1, where (a) is an SEM image of the halide solid electrolyte fiber membrane and (b) is an SEM image of the precursor fiber membrane. Detailed Implementation
[0017] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings and examples. It should be understood that the specific embodiments described herein are merely illustrative of the embodiments of the present invention and are not intended to limit the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of this application. Examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout.
[0018] It should be noted that the terms "comprising" and "having," and any variations thereof, are intended to cover non-exclusive inclusion, such as a process, method, system, product, or server that includes a series of steps or units, not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to such process, method, product, or device.
[0019] The embodiments of the present invention will now be described in detail with reference to the accompanying drawings.
[0020] like Figure 1 As shown, the preparation method of halide solid electrolyte fiber membrane includes the following steps: S1. Preparation of halide solid electrolyte precursor solution: First, dissolve the polymer in a solvent to form a three-dimensional network molecular structure; then add the halide salt and stir to mix, so that the halide salt enters the gaps in the three-dimensional network molecular structure, is uniformly wrapped and dispersed by the polymer chain, and obtains a halide solid electrolyte precursor solution with uniform molecular-level dispersion. S2. Electrospinning: The halide solid electrolyte precursor solution is electrospinned to obtain a precursor fiber membrane. During electrospinning, a constant temperature thermal field of 20℃-80℃ is applied in the spinning zone, while the temperature of the receiving device is controlled at 10℃-40℃. The fiber orientation is achieved through electrostatic stretching and traction by the receiving device, resulting in the precursor fiber membrane. The reason for the dual temperature setting of "applying a constant temperature thermal field of 20℃-80℃ in the spinning zone and controlling the temperature of the receiving device at 10℃-40℃" is as follows: The constant temperature in the spinning zone ensures the stability of the viscosity and evaporation rate of the precursor solution in the electrostatic field, avoiding uneven fiber diameter caused by temperature fluctuations; the temperature of the receiving device is lower than that in the spinning zone, allowing the fibers to solidify quickly when they fly to the receiving device, preventing the fibers from sticking and swelling on the metal roller, and ensuring the structural integrity and directional alignment of the fiber membrane. S3. Calcination: The obtained precursor fiber membrane is calcined under a protective atmosphere to obtain a halide solid electrolyte nanofiber membrane. Calcination then forms a continuous Li₂O₃ nanofiber membrane. + / Na + Ion transport channels solve the core problem of discontinuous ion transport in traditional particulate electrolytes.
[0021] Step S1 specifically includes the following steps: First, the polymer is dissolved in a solvent at a temperature of 0-100℃ and stirred continuously for 30min-480min. Then, the halide salt is added sequentially and stirring is continued for 20min-480min until all components in the system are mixed evenly to form a homogeneous precursor solution.
[0022] The halide salt mentioned in step S1 includes a lithium source or sodium source and a metal source, and the molar ratio of lithium source or sodium source, metal source, polymer and solvent is 1~4∶4~1∶0.003-0.1∶1-300.
[0023] The lithium source is at least one of lithium perchlorate, lithium carbonate, lithium acetate, and lithium chloride; The sodium source is at least one of sodium perchlorate, sodium carbonate, sodium acetate, and sodium chloride; The metal source is at least one of indium chloride, zirconium chloride, niobium chloride, ferric chloride, and lanthanum chloride; The polymer is at least one of polyvinyl butyral, polyvinyl acetate, polyvinylpyrrolidone, polyvinylidene fluoride, polyethylene oxide, and polyvinyl alcohol. Polyvinylpyrrolidone (PVP), polyvinyl butyral (PVB), and polyvinylidene fluoride (PVDF) act as fiber-forming agents. Their core function is to provide critical viscosity and elasticity to the precursor solution through molecular chain entanglement: the long polymer chains fully extend and entangle in the solvent, forming a three-dimensional network structure that uniformly encapsulates and disperses halide ions within the network structure, achieving molecular-level dispersion of halide salts and preventing halide salt aggregation. Simultaneously, the entangled molecular chains provide sufficient tensile viscosity to the precursor solution, enabling the solution to form stable Taylor cones under electrostatic forces, rather than directly breaking into droplets. This is a prerequisite for the formation of continuous fibers.
[0024] The solvent is at least one of ethanol, acetonitrile, dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, tetrahydrofuran, and water.
[0025] In step S2, the electrospinning process parameters are as follows: the relative humidity of the spinning environment is 5%-70%, the injection rate of the precursor solution is 0.1mL / h-10mL / h, the high voltage applied to the spinning field is 8kV-40kV, and the distance between the receiving device and the spinneret is 12cm-50cm.
[0026] The receiving device is a metal roller, which rotates to achieve the directional alignment of the precursor fibers.
[0027] In step S3, the specific process of heating and calcining is as follows: the calcination temperature is gradually increased from room temperature to 100℃-600℃ at a heating rate of 0.1℃ / min-10℃ / min, and then held at the highest calcination temperature for 0-480 min.
[0028] The fiber membrane prepared by the method of preparing halide solid electrolyte fiber membrane is a halide solid electrolyte fiber membrane. The average diameter of the fibers in the halide solid electrolyte fiber membrane is 50nm-800nm, and the relative standard deviation of the fiber diameter is 1%-5%. The grain size inside the fiber is 50nm-100nm. The ionic conductivity of the halide solid electrolyte fiber membrane is >10. -3 S / cm.
[0029] Application of fiber membranes in solid-state batteries.
[0030] To further disclose the present invention, the following three embodiments are added.
[0031] Example 1: Preparation of Li₂ZrCl₆ halide solid electrolyte nanofiber thin films; This embodiment prepares a flexible, densely oriented Li2ZrCl6 halide solid electrolyte nanofiber film, specifically including the following steps: S1, preparing a halide solid electrolyte precursor solution: at a temperature of 28°C, the polymer polyvinylpyrrolidone (Aladdin, molecular weight 1,300,000) is dissolved in pure water and stirred continuously for 40 min to form a three-dimensional network molecular structure; then, lithium chloride and zirconium chloride are added sequentially and stirred for another 120 min, so that the halide salt enters the gaps in the three-dimensional network molecular structure, is uniformly wrapped and dispersed by the polymer chains, until all components in the system are mixed evenly to form a homogeneous precursor solution; wherein the molar ratio of lithium source, zirconium source, polymer and solvent is 2∶1∶0.01∶5. S2. Electrospinning: The precursor solution was electrospinned to obtain a precursor fiber membrane. During electrospinning, a constant temperature thermal field of 60°C was applied in the spinning zone, while the temperature of the metal roller receiving device was controlled at 25°C. The relative humidity of the spinning environment was 70%, the injection rate of the precursor solution was 1 mL / h, the applied high voltage electric field voltage was 30 kV, the distance between the receiving device and the spinneret was 40 cm, and the rotation speed of the metal roller was 50 r / min. The fiber orientation was achieved through electrostatic stretching and traction by the metal roller. S3. Calcination: The obtained precursor fiber membrane was calcined under a nitrogen protective atmosphere. The calcination temperature was gradually increased from room temperature to 300°C at a heating rate of 3°C / min, and held at the highest calcination temperature for 60 min to obtain a Li2ZrCl6 halide solid electrolyte nanofiber film.
[0032] like Figure 2 As shown, the average diameter of the halide solid electrolyte nanofiber film prepared in this embodiment is 500 nm, and the relative standard deviation of the fiber diameter is 3%; the ionic conductivity is 1.4 × 10⁻⁶. -3 S / cm represents a flexible, dense, oriented arrangement structure.
[0033] Example 2: Preparation of Li3InCl6 halide solid electrolyte nanofiber thin film; This embodiment prepares a flexible, densely oriented Li3InCl6 halide solid electrolyte nanofiber film, specifically including the following steps: S1, preparing a halide solid electrolyte precursor solution: at a temperature of 25°C, the polymer polyvinyl butyral (Aladdin, molecular weight 170,000-250,000) is dissolved in the solvent ethanol and stirred continuously for 80 min to form a three-dimensional network molecular structure; then, lithium chloride and indium chloride are added sequentially and stirred for 120 min, so that the halide salt enters the gaps in the three-dimensional network molecular structure, is uniformly wrapped and dispersed by the polymer chains, until all components in the system are mixed evenly to form a homogeneous precursor solution; wherein the molar ratio of lithium source, indium source, polymer and solvent is 3:1:0.09:15. S2. Electrospinning: The precursor solution was electrospinned to obtain a precursor fiber membrane. During electrospinning, a constant temperature thermal field of 30°C was applied in the spinning zone, while the temperature of the metal roller receiving device was controlled at 15°C. The relative humidity of the spinning environment was 20%, the injection rate of the precursor solution was 1.5 mL / h, the applied high voltage electric field was 15 kV, the distance between the receiving device and the spinneret was 30 cm, and the rotation speed of the metal roller was 70 r / min. The fiber orientation was achieved through electrostatic stretching and traction by the metal roller. S3. Calcination: The obtained precursor fiber membrane was calcined under a nitrogen protective atmosphere. The calcination temperature was gradually increased from room temperature to 350°C at a heating rate of 5°C / min, and held at the highest calcination temperature for 120 min to obtain a Li3InCl6 halide solid electrolyte nanofiber film.
[0034] Testing revealed that the average diameter of the halide solid electrolyte nanofiber film prepared in this embodiment was 350 nm; the ionic conductivity, measured by AC impedance spectroscopy, was 2.8 × 10⁻⁶. -3 S / cm represents a flexible, dense, oriented arrangement structure.
[0035] Example 3: Preparation of Li3InCl6 halide solid electrolyte nanofiber thin film; This embodiment prepares a flexible, densely oriented Li3InCl6 halide solid electrolyte nanofiber film, specifically including the following steps: S1, preparing a halide solid electrolyte precursor solution: at a temperature of 25°C, the polymer polyvinylpyrrolidone (Aladdin, molecular weight 1,300,000) is dissolved in the solvent tetrahydrofuran and stirred continuously for 80 min to form a three-dimensional network molecular structure; then, lithium chloride and indium chloride are added sequentially and stirred for 120 min, so that the halide salt enters the gaps in the three-dimensional network molecular structure, is uniformly wrapped and dispersed by the polymer chains, until all components in the system are uniformly mixed to form a homogeneous precursor solution; wherein the molar ratio of lithium source, indium source, polymer and solvent is 3∶1∶0.09∶100. S2. Electrospinning: The precursor solution was electrospinned to obtain a precursor fiber membrane. During electrospinning, a constant temperature thermal field of 30°C was applied in the spinning zone, while the temperature of the metal roller receiving device was controlled at 15°C. The relative humidity of the spinning environment was 10%, the injection rate of the precursor solution was 1.5 mL / h, the applied high voltage electric field voltage was 15 kV, the distance between the receiving device and the spinneret was 40 cm, and the rotation speed of the metal roller was 70 r / min. The fiber orientation was achieved through electrostatic stretching and traction by the metal roller. S3. Calcination: The obtained precursor fiber membrane was calcined under a nitrogen protective atmosphere. The calcination temperature was gradually increased from room temperature to 350°C at a heating rate of 5°C / min, and held at the highest calcination temperature for 120 min to obtain a Li3InCl6 halide solid electrolyte nanofiber film.
[0036] Testing revealed that the average diameter of the halide solid electrolyte nanofiber film prepared in this embodiment was 350 nm; the ionic conductivity, measured by AC impedance spectroscopy, was 3.8 × 10⁻⁶. -3 S / cm represents a flexible, dense, oriented arrangement structure.
[0037] Example 4: Preparation of NaTaCl6 halide solid electrolyte nanofiber thin films; This embodiment prepares a flexible and dense NaTaCl6 halide solid electrolyte nanofiber film, specifically including the following steps: S1, preparing the halide solid electrolyte precursor solution: at a temperature of 80°C, the polymer polyvinylidene fluoride (Afaeza, molecular weight 570,000) is dissolved in the solvent N,N-dimethylformamide and stirred continuously for 60 min to form a three-dimensional network molecular structure; then, sodium chloride and tantalum chloride are added sequentially and stirred for another 60 min, so that the halide salt enters the gaps in the three-dimensional network molecular structure, is uniformly wrapped and dispersed by the polymer chains, until all components in the system are mixed evenly to form a homogeneous precursor solution; wherein the molar ratio of sodium source, tantalum source, polymer and solvent is 1∶1∶0.01∶100. S2. Electrospinning: The precursor solution was electrospinned to obtain a precursor fiber membrane. During electrospinning, a constant temperature thermal field of 30°C was applied in the spinning zone, while the temperature of the metal roller receiving device was controlled at 20°C. The relative humidity of the spinning environment was 45%, the injection rate of the precursor solution was 4 mL / h, the high voltage applied to the spinning field was 40 kV, the distance between the receiving device and the spinneret was 40 cm, and the rotation speed of the metal roller was 80 r / min. The fiber orientation was achieved by stretching through the electrostatic field and traction by the metal roller. S3. Calcination: The obtained precursor fiber membrane was calcined in an air atmosphere. The calcination temperature was gradually increased from room temperature to 40°C at a heating rate of 10°C / min, and held at the highest calcination temperature for 60 min to obtain a NaTaCl6 halide solid electrolyte nanofiber film.
[0038] Testing revealed that the average diameter of the halide solid electrolyte nanofiber film prepared in this embodiment was 380 nm; the ionic conductivity, measured by AC impedance spectroscopy, was 2.6 × 10⁻⁶. -3 S / cm indicates a flexible and dense structure.
[0039] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A method for preparing a halide solid electrolyte fiber membrane, characterized in that: Includes the following steps: S1. Preparation of halide solid electrolyte precursor solution: First, dissolve the polymer in a solvent to form a three-dimensional network molecular structure; then add the halide salt and stir to mix, so that the halide salt enters the gaps in the three-dimensional network molecular structure, is uniformly wrapped and dispersed by the polymer chain, and obtains a halide solid electrolyte precursor solution with uniform molecular-level dispersion. S2. Electrospinning: The halide solid electrolyte precursor solution is electrospinned to obtain a precursor fiber membrane. During electrospinning, a constant temperature hot field of 20℃-80℃ is applied in the spinning zone, while the temperature of the receiving device is controlled at 10℃-40℃. The fiber orientation is achieved by stretching the electrostatic field and pulling the receiving device to obtain the precursor fiber membrane. S3. Calcination: The obtained precursor fiber membrane is placed under a protective atmosphere and calcined to obtain a halide solid electrolyte nanofiber membrane.
2. The method for preparing a halide solid electrolyte fiber membrane according to claim 1, characterized in that: Step S1 specifically includes the following steps: First, the polymer is dissolved in a solvent at a temperature of 0-100℃ and stirred continuously for 30-480 minutes. Then, the halide salt is added sequentially and stirring is continued for 20-480 minutes until all components in the system are mixed evenly to form a homogeneous precursor solution.
3. The method for preparing a halide solid electrolyte fiber membrane according to claim 1, characterized in that: The halide salt mentioned in step S1 includes a lithium source or sodium source and a metal source, and the molar ratio of lithium source or sodium source, metal source, polymer and solvent is 1~4∶4~1∶0.003-0.1∶1-300.
4. The method for preparing a halide solid electrolyte fiber membrane according to claim 1, characterized in that: The lithium source is at least one of lithium perchlorate, lithium carbonate, lithium acetate, and lithium chloride; The sodium source is at least one of sodium perchlorate, sodium carbonate, sodium acetate, and sodium chloride; The metal source is at least one of indium chloride, zirconium chloride, niobium chloride, ferric chloride, and lanthanum chloride; The polymer is at least one of polyvinyl butyral, polyvinyl acetate, polyvinylpyrrolidone, polyvinylidene fluoride, polyethylene oxide, and polyvinyl alcohol. The solvent is at least one of ethanol, acetonitrile, dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, tetrahydrofuran, and water.
5. The method for preparing a halide solid electrolyte fiber membrane according to claim 1, characterized in that: In step S2, the electrospinning process parameters are as follows: the relative humidity of the spinning environment is 5%-70%, the injection rate of the precursor solution is 0.1mL / h-10mL / h, the high voltage applied to the spinning field is 8kV-40kV, and the distance between the receiving device and the spinneret is 12cm-50cm.
6. The method for preparing a halide solid electrolyte fiber membrane according to claim 5, characterized in that: The receiving device is a metal roller, which rotates to achieve the directional alignment of the precursor fibers.
7. The method for preparing a halide solid electrolyte fiber membrane according to claim 1, characterized in that: In step S3, the specific process of heating and calcining is as follows: the calcination temperature is gradually increased from room temperature to 100℃-600℃ at a heating rate of 0.1℃ / min-10℃ / min, and then held at the highest calcination temperature for 0-480 min.
8. The fiber membrane prepared by the method for preparing a halide solid electrolyte fiber membrane according to any one of claims 1-7, characterized in that: The fiber membrane is a halide solid electrolyte fiber membrane, and the average diameter of the fibers in the halide solid electrolyte fiber membrane is 50nm-800nm, the relative standard deviation of the fiber diameter is 1%-5%; the grain size inside the fiber is 50nm-100nm. The ionic conductivity of halide solid electrolyte fiber membranes is >10. -3 S / cm.
9. The application of the fiber membrane as described in claim 8 in solid-state batteries.
